The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0044-59672008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição ao estudo do magmatismo Paleo e Mesoproterozóico do SW do Craton Amazônico através da aplicação de isótopos estáveis de O, H e S

Abstract: RESUMO Os isótopos estáveis de O, H e S foram utilizados para investigar a origem das rochas magmáticas nos TerrenosO compatíveis com origem crustais. Análises de isótopos estáveis de H (rocha total) forneceram valores de δD entre -83‰ e -92‰, diferente das assinaturas de rochas metamórficas e de águas meteóricas. Resultados em sulfetos para isótopos estáveis de S em rochas básicas e intermediárias desta suíte apresentam valores de δ 34 S coerentes com uma fonte mantélica (entre + 0,7‰ e +3,8‰), enquanto os va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Another relevant aspect is that despite of these granites being defined as intraplate or no orogenic, some authors relate the rapakivi magmatism in Rondônia and other regions on world, like the Baltic Shield (Åhäll and Gower 1997), with the synchronous orogenic events that occurred in the region (Geraldes et al 2001;Matos et al 2004;Geraldes et al 2008;Ruiz et al 2004); Bettencourt et al (1999) believe that the youngest granites of Rondônia Tin Province (including Santa Clara and Rondônia Intrusive Suites) represent an inboard magmatism during a younger episode of reworking in the Rio Negro Juruena Province, during the final stages of the collisional Sunsás-Aguapeí orogeny (1.1 to 0.95 Ga). , comparing the idea proposed by Åhäll and Gower (1997) for the Baltic Shield case with the Amazonian Craton also suggested that an inboard bimodal rapakivi magmatism in Rondônia Tin Province could be related with the orogenic events that occurred in the southwest border of the Amazonian Craton.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant aspect is that despite of these granites being defined as intraplate or no orogenic, some authors relate the rapakivi magmatism in Rondônia and other regions on world, like the Baltic Shield (Åhäll and Gower 1997), with the synchronous orogenic events that occurred in the region (Geraldes et al 2001;Matos et al 2004;Geraldes et al 2008;Ruiz et al 2004); Bettencourt et al (1999) believe that the youngest granites of Rondônia Tin Province (including Santa Clara and Rondônia Intrusive Suites) represent an inboard magmatism during a younger episode of reworking in the Rio Negro Juruena Province, during the final stages of the collisional Sunsás-Aguapeí orogeny (1.1 to 0.95 Ga). , comparing the idea proposed by Åhäll and Gower (1997) for the Baltic Shield case with the Amazonian Craton also suggested that an inboard bimodal rapakivi magmatism in Rondônia Tin Province could be related with the orogenic events that occurred in the southwest border of the Amazonian Craton.…”
Section: Discussionmentioning
confidence: 99%
“…Rapakivi granite intrusive suites in Rondônia Tin Province have been extensively studied in recent decades [49][50][51][52][53][54][55][56][57][58][59]. Despite being primarily anorogenic, new studies [62,63] have shown that distal relationships with orogenic events may play an important role in forming these suites. The bimodal character, which was previously only suggested, through petrographic and lithogeochemical features, with the advent of new isotopic analysis techniques, mainly the U-Pb geochronological and Lu-Hf isotopic data set in zircon crystals, can now be corroborated.…”
Section: The Petrogenesis Of the Massangana Massifmentioning
confidence: 99%